2012
DOI: 10.1038/emboj.2012.35
|View full text |Cite
|
Sign up to set email alerts
|

Human mitotic chromosomes consist predominantly of irregularly folded nucleosome fibres without a 30-nm chromatin structure

Abstract: How a long strand of genomic DNA is compacted into a mitotic chromosome remains one of the basic questions in biology. The nucleosome fibre, in which DNA is wrapped around core histones, has long been assumed to be folded into a 30-nm chromatin fibre and further hierarchical regular structures to form mitotic chromosomes, although the actual existence of these regular structures is controversial. Here, we show that human mitotic HeLa chromosomes are mainly composed of irregularly folded nucleosome fibres rathe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
289
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 285 publications
(328 citation statements)
references
References 54 publications
27
289
1
2
Order By: Relevance
“…An equivalent interdigitation between the successive helical turns of 30 nm chromatin fibres was proposed previously [2,53,54], and electron microscopy [55,56], X-ray crystallography [1,4,57,58] and modelling studies [5,[25][26][27]59] indicated that nucleosomes have a high tendency to interact through their faces. Furthermore, the intense scattering peak corresponding to a spacing of approximately 6 nm found in a recent synchrotron X-ray scattering study of human mitotic chromosomes [60] also suggests a lateral association between nucleosomes in condensed chromatids. The DNA density in metaphase chromosomes is high [7,51] and edge-to-edge contacts between nucleosome cores must also be considered.…”
Section: Surface Energy Differences Of Stacked Chromatin Layers Can Ementioning
confidence: 95%
“…An equivalent interdigitation between the successive helical turns of 30 nm chromatin fibres was proposed previously [2,53,54], and electron microscopy [55,56], X-ray crystallography [1,4,57,58] and modelling studies [5,[25][26][27]59] indicated that nucleosomes have a high tendency to interact through their faces. Furthermore, the intense scattering peak corresponding to a spacing of approximately 6 nm found in a recent synchrotron X-ray scattering study of human mitotic chromosomes [60] also suggests a lateral association between nucleosomes in condensed chromatids. The DNA density in metaphase chromosomes is high [7,51] and edge-to-edge contacts between nucleosome cores must also be considered.…”
Section: Surface Energy Differences Of Stacked Chromatin Layers Can Ementioning
confidence: 95%
“…Nevertheless, although the fiber is well characterized in vitro, the question of its in vivo significance is still much debated (Maeshima et al 2010;Fussner et al 2011;Hansen 2012;Ghirlando and Felsenfeld 2013). In particular, no higher order structures, including the 30-nm fiber, are observed by cryo-electron microscopy in native mitotic chromosomes (Eltsov et al 2009;Nishino et al 2012), nor are they apparent in nuclei of tissue-culture cells analyzed by correlative electron spectroscopic imaging (Ahmed et al 2010). As originally described, the 30-nm fibrr contains one or more helical stacks of nucleosomes with an eponymous diameter of approximately 30 nm (Finch and Klug 1976) (Fig.…”
Section: -Nm Fibermentioning
confidence: 99%
“…General consensus is that chromatin probably adopts dynamically a mix of structures depending on the cell activity [158,159]. This fluidity helps the cell to modulate chromatin accessibility and accordingly the DNA expression level [158], but complicates the theoretical description of the in vivo chromatin structure.…”
Section: Mesoscopic Studiesmentioning
confidence: 99%
“…This fluidity helps the cell to modulate chromatin accessibility and accordingly the DNA expression level [158], but complicates the theoretical description of the in vivo chromatin structure. Despite recent advances, even coarse-grained methods are unable to manage the size and complexity of chromatin.…”
Section: Mesoscopic Studiesmentioning
confidence: 99%